Spin-lattice-dynamics analysis of magnetic properties of iron under compression - Gonzalo dos Santos; Robert Meyer; Diego Tramontina; Eduardo M. Bringa; Herbert M. Urbassek (Scientific Reports, 2023)
Abstract Compression of a magnetic material leads to a change in its magnetic properties. We examine this effect using spin-lattice dynamics for the special case of bcc-Fe, using both single- and poly-crystalline Fe and a bicontinuous nanofoam structure. We find that during the elastic phase of compression, the magnetization increases due to a higher population of the nearest-neighbor shell of atoms and the resulting higher exchange interaction of neighboring spins. In contrast, in the plastic phase of compression, the magnetization sinks, as defects are created, increasing the disorder and typically decreasing the average atom coordination number. The effects are more pronounced in single crystals than in polycrystals, since the presence of defects in the form of grain boundaries counteracts the increase in magnetization during the elastic phase of compression. Also, the effects are more pronounced at temperatures close to the Curie temperature than at room temperature. In nanofoams, the effect of compression is minor since compression proceeds more by void reduction and filament bending—with negligible effect on magnetization—than by strain within the ligaments. These findings will prove useful for tailoring magnetization under strain by introducing plasticity.